2016
DOI: 10.1038/srep37129
|View full text |Cite
|
Sign up to set email alerts
|

Odour-induced analgesia mediated by hypothalamic orexin neurons in mice

Abstract: Various folk remedies employ certain odorous compounds with analgesic effects. In fact, linalool, a monoterpene alcohol found in lavender extracts, has been found to attenuate pain responses via subcutaneous, intraperitoneal, intrathecal, and oral administration. However, the analgesic effects of odorous compounds mediated by olfaction have not been thoroughly examined. We performed behavioural pain tests under odourant vapour exposure in mice. Among six odourant molecules examined, linalool significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 56 publications
(72 reference statements)
0
36
0
Order By: Relevance
“…A study by Tashiro and collaborators [ 65 ] reported the antinociceptive effect of linalool in a different experimental protocol using vapour exposure mediated by hypothalamic orexin neurons, one of the main mediators in the behavioral responses to pain [ 66 ]. The involvement of these cells was evidenced by a significant increase in the number of c-Fos-expressing orexin neurons, and in linalool odour-exposed and odourless air-exposed orexin neuron-ablated mice that exhibited similar pain behavior in the first and second phase of the formalin test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Tashiro and collaborators [ 65 ] reported the antinociceptive effect of linalool in a different experimental protocol using vapour exposure mediated by hypothalamic orexin neurons, one of the main mediators in the behavioral responses to pain [ 66 ]. The involvement of these cells was evidenced by a significant increase in the number of c-Fos-expressing orexin neurons, and in linalool odour-exposed and odourless air-exposed orexin neuron-ablated mice that exhibited similar pain behavior in the first and second phase of the formalin test.…”
Section: Resultsmentioning
confidence: 99%
“…In the investigation of the participation of olfactory processing in linalool analgesic effects by chemical nociceptive stimulus (formalin test), pain behavior in olfactory bulbectomized mice under linalool vapour exposure did not differ markedly from the odourless air group in both phases of the test. In the anosmic model using mice with a nonfunctional olfactory epithelium, no effects of linalool vapour were observed, providing further evidence that the olfactory response produced by linalool vapour may play a key role in inducing analgesic effects [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…In control group, 10 mL/kg of corn oil was administered by intraperitoneal injection in control group. Two weeks after the injection, 3-MI treated mice were used for the behavioral test (Tashiro et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Though no study has investigated its effect independently in neuropathic pain models, animal social enrichment alone has been demonstrated to reduce the duration of inflammatory pain . Of note, EE studies on inflammatory, thermal, or muscle pain models used a greater variety of stimulations, such as odor, tactile, or animal handling, but it is beyond the scope of our review. It is anticipated that a more diverse range of EE modalities will be tested in future studies.…”
Section: Experimental Limitations and Future Perspectives In Animal Smentioning
confidence: 99%